Crystallization of polycarbonate in solvent/nonsolvent system and its application to high‐density polyethylene composite as a filler. Issue 8 (29th August 2013) - Hwang, Duck Kun; Lee, Heon Sang; Kim, Hyun Jong; Shul, Yong Gun; Oh, Kyeongseok
<x xml:space="preserve">Abstract</x> Crystallization of polycarbonate (PC) was attempted by a precipitated method in a ternary system of PC/solvent/nonsolvent. Chloroform was used as a solvent, and isopropanol was used as a nonsolvent. Crystallization of PC was clearly observed as a powdery state when chloroform/isopropanol mixtures were prepared by 68/32 and 61/39 vol%. Crystallinity of PC was evaluated by differential scanning calorimeter and X‐ray diffractometer. As the difference of solubility parameters between PC and binary solvent/nonsolvent mixtures became smaller, the relative crystallinity of PC was increased. The highest degree of PC crystallization was obtained when chloroform/isopropanol was mixed by 61/39 vol%. Subsequently, crystallized PC was used as a filler to high‐density polyethylene (HDPE) composite. HDPE composite incorporated by crystallized PC filler improved its mechanical and thermal properties. Flexural modulus was increased from 620 to 990 N/mm2, and flexural strength was increased from 720 to 1080 N/mm2. And heat deflection temperature measurement and flammability test supported the enhancement of thermal property when crystallized PC was added to HDPE composite up to 40 wt%. POLYM. ENG. SCI., 54:1893–1899, 2014. © 2013 Society of Plastics Engineers